Analysis of Students' Scientific Literacy Skill in terms of Gender Using Science Teaching Materials Discovery Model Assisted by PhET Simulation - Bahtiar, B.; Ibrahim, I.; Maimun, M. (Jurnal Pendidikan IPA Indonesia, 2022)
This study aimed to analyze scientific literacy skills in terms of gender using discovery model science teaching materials assisted by PhET simulation. This study is a one-group pretest and posttest design and an experimental. This research was conducted at MTs Hidayatullah Mataram in class IXA students in three meetings for 80 minutes each. The material used is static electricity which consists of five sub materials, namely static electricity, atoms, electric charge, Coulomb's law, and electroscope. The collection method of the scientific literacy test is in the form of multiple-choice with the indicators of being to explain scientific phenomena, scientific discoveries, and statements, and use scientific data and evidence. Prior to use, a feasibility test was carried out. The results of the item analysis show that people have a good level of adjustment, reliability, and difficulty level. The research found that: (1) female and male students had different scientific literacy skills, where the scientific literacy skill of female students was higher (80) than male students (77.95); (2) there were three sub-materials dominated by female students, namely the sub-materials of electrical charge, Coulomb's Law, and electroscope; (3) there are two sub-materials of static electricity which are dominated by male students, namely the sub-materials of static electricity and atoms; (4) in the average percentage of the indicator of explaining phenomena scientifically and interpreting data and evidence scientifically, female students are higher than male students; and (5) the average percentage of evaluating and designing scientific statements is higher for male students than female students. Suggestions for teachers are to pay attention to the roles of female and male students in the learning process so that the abilities of female and male students are not much different.